Analisis Non Perfoming Loan (Npl), Biaya Operasional Dan Pendapatan Opersional (Bopo) Dan Capital Adequacy Ratio (Car) Terhadap Return On Asset (Roa) Pada Bank Bumn Yang Terdaftar Di Bei Periode 2013-2022 - Ainun, Nur (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
The purpose of this research is to determine the effect of Non Performing Loan (NPL), Operating Cost and Operating Income (BOPO) and Capital Adequacy Ratio (CAR) on Retrun On Asset (ROA). The method used in this study is non probability sampling, the sampels used in this study were 40 at state owned banks for the 2013-2022 period. The results of this study based on the T test show that Capital Adequacy Ratio (CAR) has a positive an significant effect on Return On Asset (ROA), Non Perfrming Loan (NPL) has a negative an significant effect on Return On Asset (ROA), Operating Costs and Operating Income (BOPO) have a negative and significant effect on Return On Asset (ROA).